Revision of the Lithoglyptidae sensu Tomlinson, 1969 and Lithoglyptes Aurivillius, 1892 (Cirripedia, Acrothoracica,), including a new species from Bermuda - Kolbasov, Gregory A.; Newman, William A. (Zootaxa, 2005)
The morphology of the females and males of the ancient acrothoracican burrowing barnacle family, the Lithoglpytidae Aurivillius, 1892, was surveyed. It became evident that by resurrecting a previously described family-group taxon and proposing a new family-group taxon, the Lithoglyptidae could readily be divided into three subfamilies, the Lithoglyptinae s.s. Aurivillius, 1892 stat. nov., the Weltneriinae subfam. nov., and the Kochlorininae Gruvel, 1905 stat. nov. The largest and relatively generalized lithoglyptine genus, Lithoglyptes s.l., was investigated utilizing SEM as well as conventional means. From gross morphological characteristics it became evident these species fell into three natural groups for which we propose the genera Lithoglyptes s.s., Auritoglyptes gen. nov., and Armatoglyptes gen. nov. The relationships between the species as well as the genera are explored cladistically, a new species of Armatoglyptes is described from Bermuda, the biogeography of the subfamily is discussed, and a key to the genera and species is provided.